Who is Mobilized to Vote by Short Text Messages? Evidence from a Nationwide Field Experiment with Young Voters - Hirvonen, Salomo; Lassander, Maarit; Sääksvuori, Lauri; Tukiainen, Janne (Springer Nature, 2025)
Using a large randomized controlled trial and rich individual-level data on eligible voters and their household members, we evaluate how get-out-the-vote (GOTV) appeals affect inequalities in voting, transmit from treated to untreated individuals within households, and how the transmission of voting decisions through family networks influences inequalities in voting. We find that receiving a text message reminder before the Finnish county elections in 2022 mobilized mainly low-propensity voters. As a result, the GOTV intervention reduced existing social inequalities in voting within the target group of young voters. We remarkably find that over 100% of the direct treatment effect spilled over to untreated household members. These spillovers reduced inequality in political participation among the older voters who were not part of the target group. Overall, our results exemplify how randomized controlled trials with a limited focus on the analysis of individuals in the treatment and control groups alone may lead to misestimating the compositional effects of get-out-the-vote interventions.